Global, regional, and national trends in colorectal cancer burden from 1990 to 2021 and projections to 2040 - Tao Zhang; Yuchen Guo; Binxu Qiu; Xianyu Dai; Yifei Wang; Xueyuan Cao (Frontiers in Oncology)
BackgroundColorectal cancer (CRC) is a common malignancy with notable recent shifts in its burden distribution. Current data on CRC burden can guide screening, early detection, and treatment strategies for efficient resource allocation.MethodsThis study utilized data from the latest Global Burden of Diseases, Injuries, and Risk Factors (GBD) Study. Initially, a series of descriptive statistics were performed on the incident cases, deaths, disability-adjusted life years (DALYs), and age-standardized rates (ASRs) of CRC. Percentage changes and average annual percentage changes (AAPC) were then calculated to understand the trends in CRC disease burden. Decomposition and frontier analyses were conducted, and finally, the Bayesian age-period-cohort (BAPC) model was used to predict changes in ASRs up to 2040.ResultsThe GBD 2021 estimates indicate a significant increase in the global incident cases, deaths, and DALYs of CRC from 1990 to 2021. The age-standardized incidence rate (ASIR) increased (AAPC: 0.2), while the age-standardized mortality rate (ASMR) (AAPC: -0.72) and age-standardized DALYs rate (AAPC: -0.73) decreased. Males bore a higher disease burden than females, though the trends in disease burden changes were similar for both sexes. Although developed regions had higher incident cases, deaths, and DALYs, they showed more significant declines in ASRs. Decomposition analysis revealed that population growth and aging were the primary drivers of the increased disease burden. Frontier analysis showed that as the Socio-demographic Index increased, the disparity in CRC ASRs among countries widened, with developed regions having greater potential to reduce these rates. The By 2040, the BAPC model projects significant declines in global ASMR and age-standardized DALYs rates, while ASIR is expected to decrease in females but increase in males and across both sexes.ConclusionCRC remains a significant public health issue with regional and gender differences, necessitating region- and population-specific prevention strategies.